(untitled) (American Journal of Interdisciplinary Research and Development, 2023)
In this article, research was conducted within the framework of the project on improving the teaching of programming and artificial intelligence in the field of computer science and information technology for upper classes of general secondary education. Within the framework of the project, it is planned to establish a laboratory in 12 schools in Tashkent, improve the qualifications of teachers and develop educational content. In order to determine the relevance of the project, a survey on programming and artificial intelligence was conducted in 12 schools in Tashkent with the participation of 10th and 11th grade students and their parents, teachers of relevant subjects and school principals. Models for analyzing the results of school surveys were researched. Similarly, the state of training and introduction of personnel in the field of artificial intelligence in Uzbekistan was analyzed.